POLA HIDUP MASYARAKAT LINGKUNGAN CANDI BOROBUDUR - Suharto Suharto (Jurnal Penelitian Humaniora, 2003)
Abstract For Indonesia the tourism industry is an opportunity, which cannot be released freely. Tourism has been growing to be an advantageous industry, which has a good prospect for the national development. Borobudur Temple is one of the cultural heritages, which is visited by foreign and domestic tourists in which the number increases every year. Every country or tourism resort has its typical and interesting custom, which is the mainstay of the tourism. Borobudur Temple is located in Borobudur Village, is a Buddhists cultural remain, and the society around it has a unique traditional dance namely “Kobra Siswo” and “Dayakan”, which has dynamic movements and a typical custom, and which attract visitors. The manner of life today will be a culture in the future. So, the manner of life of the society around Borobudur Temple is necessary to promote and it will be an interesting factor for the tourists, especially because of the difference culture between that of the foreign tourists and of the society around Borobudur Temple, which is the center of crafts developing. This research aims at giving a contribution in the form of thought in order to develop crafts, which can be developed together with the tourism development and the culture heritage. So, it is hoped that the living standard of the society around Borobudur Temple and the foreign exchange of country will increase.